6(x+2)=2(3x+8)-4

Simple and best practice solution for 6(x+2)=2(3x+8)-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x+2)=2(3x+8)-4 equation:


Simplifying
6(x + 2) = 2(3x + 8) + -4

Reorder the terms:
6(2 + x) = 2(3x + 8) + -4
(2 * 6 + x * 6) = 2(3x + 8) + -4
(12 + 6x) = 2(3x + 8) + -4

Reorder the terms:
12 + 6x = 2(8 + 3x) + -4
12 + 6x = (8 * 2 + 3x * 2) + -4
12 + 6x = (16 + 6x) + -4

Reorder the terms:
12 + 6x = 16 + -4 + 6x

Combine like terms: 16 + -4 = 12
12 + 6x = 12 + 6x

Add '-12' to each side of the equation.
12 + -12 + 6x = 12 + -12 + 6x

Combine like terms: 12 + -12 = 0
0 + 6x = 12 + -12 + 6x
6x = 12 + -12 + 6x

Combine like terms: 12 + -12 = 0
6x = 0 + 6x
6x = 6x

Add '-6x' to each side of the equation.
6x + -6x = 6x + -6x

Combine like terms: 6x + -6x = 0
0 = 6x + -6x

Combine like terms: 6x + -6x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 3x+4-5x-14=10 | | 7d-4d-4d-6=2d | | 11x+2=14x-10 | | 10y=40x+3xy | | 2(t-2)=6 | | 7x-y=(x) | | 0.5(x+2)-(3x+8)=1.6(x-2)+9 | | 3(7x+20Y)+7(-3x+6y)= | | y-37=-67 | | -21=n-10 | | 2(2x+5)=40 | | 3(x-5)=2(x+1)+x | | 5+9x=-13 | | -5.7-44.2=-8.3v | | -7y+3=8y+1 | | 3(7x+20Y)7(-3x+6y)= | | 4x+8-3x-10=-33 | | -6-2x-1=4x+8-6x-3 | | 2(n+5)=11 | | 7=-11+3(6+5) | | 2(n+5)=111 | | -5r-r=5r-8 | | 3x+5x+4x-2=10 | | -10x+8-6x=-2-17x+9 | | 5.4x+8.6=3.4x-16 | | (10+2x)(20+2x)=336 | | 7x+6=3x+2 | | 2x-16y=7 | | 6(6g-2)+8(1+5g)=2g | | 6n-32=3n+7 | | 2x^2-4x=1.33333 | | 7t-6=330 |

Equations solver categories